Improved cooperative spectrum sensing scheme based on dempster-shafer theory in cognitive radio network - Mei-ting YU; Lin-jing ZHAO; Zhao LI (Tongxin xuebao)
An improved cooperative spectrum sensing scheme based on dempster-shafer evidence theory in cognitive radio networks was proposed.In the local sensing period,the projection approximation algorithm was introduced to reduce bandwidth for cooperation.In the fusion period,credibility was calculated by the distance between evidence vectors of different secondary users and adopted as the weights to combine different local sensing data.The new scheme reduces channel bandwidth and simulation results show that the new scheme improves the performance under the condition of high level conflict.